Development of efficient bi-functional g-C3N4@MOF heterojunctions for water splitting. Issue 49 (10th November 2022) - Fiaz, Muhammad; Carl, Nkenku; Kashif, Muhammad; Farid, Muhammad Asim; Riaz, Nagina Naveed; Athar, Muhammad
Abstract : Highly efficient heterojunctions by combining n-type g-C3 N4 and MOFs as bi-functional photoelectrocatalysts towards the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). Abstract : Herein we report the development of highly efficient heterojunctions by combining n-type g-C3 N4 and MOFs as bi-functional photoelectrocatalysts towards the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). g-C3 N4 @MIL-125(Ti) and g-C3 N4 @UiO-66 have been synthesized via in situ incorporation of pre-synthesized g-C3 N4 nanoparticles into MIL-125(Ti) and UiO-66. Bare MIL-125(Ti) and UiO-66 are also prepared for comparison. All the synthesized samples have been characterized by Powder X-ray Diffraction analysis, Fourier Transform Infrared Spectroscopic analysis, Scanning Electron Microscopic analysis, Energy Dispersive X-ray Spectrometry and UV-Vis Spectroscopic analysis. Cyclic voltammetry and linear sweep voltammetry studies have been carried out for all samples which indicates that under visible light exposure the g-C3 N4 @MIL-125(Ti)/NF heterojunction achieved a current density of 10 mA cm −2 at just 86 and 173 mV overpotential for the HER and OER, respectively. Moreover, all the synthesized samples display significant stability and generate a constant current density up to 1000 cyles during water electrolysis performed at a constant applied potential 1.5 V.